The relationship between sports psychology, self-motivation and educational attainment level at university-level education in China - Fang Zheng (Revista de Psicología del Deporte (Journal of Sport Psychology), 2022)
With the rapid growth of competitive sports and the rising intense competition trend, the sports circle across the world increases specific skill training. This research study measures the relationship between sport psychology, self-motivation, a, and educational attainment. This research study was conducted in China and is based on primary research. For gathering the data used different questions related to the variables. The sport psychology, self-motivation, and educational attainment are the main independent variables and through the university level education measure the relationship between them, for measuring the data analysis, used smart PLS software and run basic results related to sport psychology. The smart PLS algorithm model, parameter estimated result, correlation coefficient, and histogram analysis. Results found significant and positive relationships between sports psychology, self-motivation, and educational attainment levels. It gradually emphasizes the training and intervention of students related to sport' psychological abilities. Therefore, this study has significance for knowing which qualities may aid athletes in developing strong attention control.